PENGEMBANGAN EKONOMI LOKAL UNTUK MENINGKATKAN DAYA SAING PADA UKM EKONOMI KREATIF BATIK BAKARAN DI PATI, JAWA TENGAH - Ghalib Agfa Polnaya; Darwanto Darwanto (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2015)
The purpose of this study is to establish the SME development strategy of creative economy, batik burnt in Pati, Central Java, to improve competitiveness. SMEs of creative economy of burnt batik are felt capable of developing the local economy of the surrounding community through science, creativity, and innovation. SMEs are also considered to be able to develop jobs. However, the SMEs of creative economy of burnt batik are unable to give special characteristics to the Pati itself. This study uses Analytical Network Process (ANP). Analysis of the development strategy of competitiveness in SMEs kreati burnt batik covering aspects of the industry, technology, resources, institutions, and financial intermediation. ANP analysis results shows that the five aspects of competitiveness developer in the SME creative burnt batik can generate the resources as a top priority and the development of appropriate strategies to improve the quality of human resources in hopes can help the use of renewable raw materials. Recommended strategies for improving the quality of creative human resources is a strategic with the highest priority with a score of 0.2329. Keywords: Batik Bakaran, SMEs, Creative Economy, The Local Economy, ANP (Analytical Network Process)